1990
DOI: 10.1126/science.2251501
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of gp120 from HIV-1 Virions Induced by Soluble CD4

Abstract: The CD4 antigen is the high affinity cellular receptor for the human immunodeficiency virus type-1 (HIV-1). Binding of recombinant soluble CD4 (sCD4) or the purified V1 domain of sCD4 to the surface glycoprotein gp120 on virions resulted in rapid dissociation of gp120 from its complex with the transmembrane glycoprotein gp41. This may represent the initial stage in virus-cell and cell-cell fusion. Shedding of gp120 from virions induced by sCD4 may also contribute to the mechanism by which these soluble recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
478
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 575 publications
(509 citation statements)
references
References 40 publications
29
478
2
Order By: Relevance
“…The differential loss of gp120 between X4-and R5-tropic HIV-1 may be due to differences in the inherent stability of the gp120-gp41 complex, or to differences in gp120 conformational changes induced upon CD4 binding. Previous studies have shown that laboratoryadapted strains of HIV-1, which are generally X4-tropic, readily shed gp120 upon addition of soluble CD4 and are more sensitive to inhibition by sCD4 (31,36,50,61). The preferential inhibition of X4-tropic HIV-1 by sCD4 is also in general agreement with the hypothesis that cellular CD4 is more detrimental for replication of X4-tropic HIV-1.…”
Section: Discussionsupporting
confidence: 77%
“…The differential loss of gp120 between X4-and R5-tropic HIV-1 may be due to differences in the inherent stability of the gp120-gp41 complex, or to differences in gp120 conformational changes induced upon CD4 binding. Previous studies have shown that laboratoryadapted strains of HIV-1, which are generally X4-tropic, readily shed gp120 upon addition of soluble CD4 and are more sensitive to inhibition by sCD4 (31,36,50,61). The preferential inhibition of X4-tropic HIV-1 by sCD4 is also in general agreement with the hypothesis that cellular CD4 is more detrimental for replication of X4-tropic HIV-1.…”
Section: Discussionsupporting
confidence: 77%
“…56 The protein content of the resultant lentiGFP was measured using bicinchoninic acid and titers determined by p24 enzyme-linked immunosorbent assay (Aalto, Bio Reagents Ltd, Dublin, Ireland). 57 Viral titer is presented as an M.O.I. ratio defined as the number of infectious virus particles deposited in a tissue culture well divided by the number of cells present in the well.…”
Section: Methodsmentioning
confidence: 99%
“…A twin-site sandwich ELISA was performed essentially as described (15). Briefly, a polyclonal Ab was adsorbed to a solid phase to capture p24 Ag from a detergent lysate of virions.…”
Section: Hiv P24 Capsid Ag (P24) Elisamentioning
confidence: 99%